The effect of three liquid bio-fertilizers in the production of lettuce (lactuca sativa l.) and cabbage (brassica oleracea l. var. capitata (2011)
In modern agriculture, the use of agrochemicals has grown considerably, increasing production costs and causing serious problems for the environment. The use of bio-fertilizers is a viable alternative to improve the profitability of crops, particularly for agriculture on medium and small-sized farms with intensive production systems, such as vegetables. Given that bio-fertilizers can be produced on the farm and used successfully in crop production, this research focused on the effect of three bio-fertilizers on the production of lettuce and cabbage, biweekly applications were made with liquid fertilizers produced from the manure of cows (BFC), guinea pigs (BFGp) and pigs (BFPi) and compared to a commercial foliar fertilizer (CFF) and a control without an application. We observed the presence of Lactobacillus and Saccharomyces in the BFC and BFGp fertilizers and Bacillus in the BFPi fertilizer. The weight and head diameter and yield of lettuce and cabbage favored the bio-fertilizer applications compared to the control, but no statistical differences were found compared to the commercial foliar fertilizer (CFF). This behavior is attributed not only to the mineral content, but also to the presence of metabolite regulators of plant physiology, produced by the microbial action of the bio-fertilizers.